Numerous Conserved and Divergent MicroRNAs Expressed by Herpes Simplex Viruses 1 and 2 - Jurak, Igor (American Society for Microbiology (ASM), 2010)
Certain viruses use microRNAs (miRNAs) to regulate the expression of their own genes, host genes, or both. Previous studies have identified a limited number of miRNAs expressed by herpes simplex viruses 1 and 2 (HSV-1 and -2), some of which are conserved between these two viruses. To more comprehensively analyze the miRNAs expressed by HSV-1 or HSV-2 during productive and latent infection, we applied a massively parallel sequencing approach. We were able to identify 16 and 17 miRNAs expressed by HSV-1 and HSV-2, respectively, including all previously known species, and a number of previously unidentified virus-encoded miRNAs. The genomic positions of most miRNAs encoded by these two viruses are within or proximal to the latency-associated transcript region. Nine miRNAs are conserved in position and/or sequence, particularly in the seed region, between these two viruses. Interestingly, we did not detect an HSV-2 miRNA homolog of HSV-1 miR-H1, which is highly expressed during productive infection, but we did detect abundant expression of miR-H6, whose seed region is conserved with HSV-1 miR-H1 and might represent a functional analog. We also identified a highly conserved miRNA family arising from the viral origins of replication. In addition, we detected several pairs of complementary miRNAs and we found miRNA-offset RNAs (moRs) arising from the precursors of HSV-1 and HSV-2 miR-H6 and HSV-2 miR-H4. Our results reveal elements of miRNA conservation and divergence that should aid in identifying miRNA functions.